Motivasi, Lingkungan Keluarga dan Pendidikan Kewirausahaan Terhadap Minat Berwirausaha Mahasiswa - Purnamiadi, Ni Komang Febi; Wirajaya, I Gde Ary (E-Jurnal Akuntansi, 2021)
Fostering the entrepreneurial spirit of college students can be an alternative to reduce unemployment. The growth of the entrepreneurial spirit of students is expected to create job opportunities after graduating from college. The purpose of this study was to determine the effect of motivation, family environment and entrepreneurship education on the entrepreneurial interest of accounting students. The sample used was 160 students of the Accounting Study Program, Faculty of Economics and Business, Udayana University class 2017. The sampling technique was purposive sampling technique. The analytical tool used is multiple linear regression. The results showed that entrepreneurial motivation had a positive effect on interest in entrepreneurship, the family environment had a positive effect on interest in entrepreneurship and entrepreneurship education had a positive effect on interest in entrepreneurship. Keywords : Motivation; Family Environment; Entrepreneurship Education; Entrepreneurial Interest.